دراسة حول أفضل المواقع القابلة لتوليد الطاقة الشمسية في الجمهورية اليمنية: د. عبد الجبار محمد صالح العياني ، أ. د. نبيل عبد الله نعمان القدسي - مجلة الأندلس للعلوم التطبيقية د. عبد الجبار محمد صالح العياني ، أ. د. نبيل عبد الله نعمان القدسي (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN Astronomical Site for Yemen shows that the territory of the Republic of Yemen is located within ideal areas for generating solar energy. , but unfortunately has not taken advantages of it as a source of energy economically so far, so it was necessary to carry out a study on the solar radiation and the factors., influencing it for several areas within the four geographical regions for Yemen in order to choose the best ideal locations for the solar station in Yemen. The results indicatedto the existence ofseveral locationswell suited to be solar station. Marib Directorate represents the optimal governorate and the best guide of the most promising sources to exploitation